The Use of Artificial Intelligence Based Technology in English Language Teaching - A. Anggraini; F. Faisal (Manunggal Halim Jaya, 2024)
Artificial Intelligence (AI) is a technology that enables computers and machines to simulate learning, understanding, problem-solving, decision-making, creativity, and computer-based human intelligence. AI is also one of the driving forces of the Industry 4.0 revolution to facilitate education in the teaching and learning process. This research aims to understand the role of AI in English Language Teaching (ELT) and to investigate AI technologies in ELT. This is a library research study. The results show that AI offers a conducive learning environment for English language learning. It has significant capabilities to create a personalized environment where learners use their senses to simultaneously practice English skills depending on their current English proficiency level, vocational needs, or interests. AI provides a real-life simulation platform for dialogue, such as spoken English, and enhances practical skills like writing. It increases students' practice capacity and optimizes the impact of English teaching in ELT. Learning English has become easier with the development of technology and platforms. AI technology offers opportunities to enhance English language skills. The availability of various learning technologies makes it easier for students to understand English. There are many AI-based ELT applications available for students to use. This technology, as a smart machine that thinks and behaves like humans, can simulate intelligence and make decisions similar to human reasoning through processes on computers or mobile phones, such as Google Translate, Able Platform, Orai, Elsa, Chatbot, Duolingo, Hello English Apk, and many others.